2001
DOI: 10.1901/jeab.2001.76-289
|View full text |Cite
|
Sign up to set email alerts
|

Habituation Contributes to Within‐session Changes in Free Wheel Running

Abstract: Three experiments tested the hypothesis that habituation contributes to the regulation of wheel running. Rats ran in a wheel for 30-min sessions. Experiment 1 demonstrated spontaneous recovery. Rats ran more and the within-session decreases in running were smaller after 2 days of wheel deprivation than after 1 day. Experiment 2 demonstrated dishabituation. Running rate increased immediately after the termination of a brief extra event (application of the brake or flashing of the houselight). Experiment 3 demon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(19 citation statements)
references
References 36 publications
2
16
1
Order By: Relevance
“…References to dishabituation apply particularly to studies of odor discrimination (Brown, 1988;Schellinck et al, 1995). While strictly speaking such terminology may be appropriate especially with activity (rather than choice) measures of responsiveness to novel stimulation (Aoyama and McSweeney, 2001;Terry, 1979), in the case of active choices of novel stimuli it is debatable if it is more informative than merely describing them as investigation of novelty, particularly since habituation (and presumably dishabituation) of neotic behavior may be a different phenomenon from habituation of orienting or reflexive responses (see above).…”
Section: Habituation To Noveltymentioning
confidence: 99%
“…References to dishabituation apply particularly to studies of odor discrimination (Brown, 1988;Schellinck et al, 1995). While strictly speaking such terminology may be appropriate especially with activity (rather than choice) measures of responsiveness to novel stimulation (Aoyama and McSweeney, 2001;Terry, 1979), in the case of active choices of novel stimuli it is debatable if it is more informative than merely describing them as investigation of novelty, particularly since habituation (and presumably dishabituation) of neotic behavior may be a different phenomenon from habituation of orienting or reflexive responses (see above).…”
Section: Habituation To Noveltymentioning
confidence: 99%
“…Studies on dishabituation showed that one stimulus can be considered as an effective dishabituator when it induces a response, different, or not, from the response produced by the habituatory stimulus. In other words, all stimuli, that are sufficiently intense to produce an increase in the state of vigilance, are able to produce dishabituation of the habituated response (Groves and Thompson 1970;Mongeluzi and Frost 2000;Aoyama and McSweeney 2001). So, the absence of dishabituation in our experiments cannot be due to chosen dishabituatory stimuli (crab, flashing light) because an increase in the state of arousal of the cuttlefish was universally observed with the two stimuli.…”
Section: Discussionmentioning
confidence: 64%
“…In studies with rats, Groves and Thompson (1970) trained animals to inhibit startle response to repeated acoustic stimulation, presenting 17 habituation stimuli at 1-min intervals; they reported that the rats showed recovery of the response immediately after a novel stimulus (flashing light) given between the 14th and the 15th habituation trial. Rats given a 30-min session in a running wheel each day over a 20-d training period (Aoyama and McSweeney 2001) showed dishabituation immediately after a brief extra event (the application of a brake or a flashing of the house light) lasting 5 sec, given 20 min 55 sec after the beginning of a free running session. In Aplysia, Marcus et al (1988) obtained an increase in siphon withdrawal reflex 90 sec after the administration of an arousing stimulus (mild tactile stimulus) given just after habituation (20 habituation stimuli at 30-sec intervals).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Changing the reinforcer for a brief time late in the session increases the response rate once the original reinforcer is restored (Aoyama & McSweeney, 2001a;McSweeney & Roll, 1998). The response rate increases regardless of whether the change is an increase or a decrease in the amount of reinforcer delivered and regardless of whether the change produces an increase or a decrease in response rate while it is in effect.…”
Section: Discussionmentioning
confidence: 97%